Comparative evaluation of the efficacy of chemomechanical caries removal agent (Papacarie) and conventional method of caries removal: An in vitro study - Jawa D; Singh S; Somani R; Jaidka S; Sirkar K; Jaidka R (Wolters Kluwer Medknow Publications, 2010)
Painless dentistry, minimal intervention and thus giving comfort, relief and solace and instill positive attitude toward dental treatments, are some of the factors justifying the specialty of pediatric dentistry. Thus, this in vitro study was undertaken to compare the efficacy of a new chemomechanical caries removal agent, Papacarie (Formula and Acao), with conventional slow-speed rotary instrument (bur). Papacarie is a new formulation and has the main active ingredient papain, an endoprotein with bactericidal, bacteriostatic and anti-inflammatory actions. Twenty extracted human molar teeth with deep dentine caries and no enamel coverage were selected for the study. After the preparation of the teeth and removal of the caries with the respective methods, they were decalcified, dehydrated and embedded in paraffin blocks for histologic studies. Serial sections of 5 μm thickness were examined for the presence of bacteria under light microscope. Though complete removal of caries was achieved significantly in both the methods, there was less marked destruction of dentinal tubules in chemomechanical caries removal method by Papacarie. Thus, Papacarie is recommended as an efficient, easy to perform, comfortable and less destructive solution for the patient seeking an alternative to the conventional method.